2015
DOI: 10.1093/ckj/sfv060
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the physical and emotional impact of early-stage ADPKD: experiences and perspectives of patients and physicians

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary renal disorder; however, at the time this research was conducted, no disease-modifying treatment was currently available. Medical texts often describe early-stage disease (Stages 1 and 2) as asymptomatic, but there is evidence from patients of considerable physical and emotional effects.MethodsIn-depth interviews were conducted with 80 ADPKD patients, 72 nephrologists and 85 primary care physicians (PCPs) from nine Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Learning the patient perspective of their most prevalent and disabling symptom(s) that they themselves prioritize for treatment is essential in PMDs that have such high phenotypic heterogeneity. This result is unique to PMD due to the multi-systemic nature of this disease, in contrast to studies in other rare inherited disorders [ 32 , 33 ]. Awareness of discrepancies in physician-patient or physician-parent perceptions of disease burden need to be acknowledged and considered in trial design [ 34 ].…”
Section: Discussionmentioning
confidence: 80%
“…Learning the patient perspective of their most prevalent and disabling symptom(s) that they themselves prioritize for treatment is essential in PMDs that have such high phenotypic heterogeneity. This result is unique to PMD due to the multi-systemic nature of this disease, in contrast to studies in other rare inherited disorders [ 32 , 33 ]. Awareness of discrepancies in physician-patient or physician-parent perceptions of disease burden need to be acknowledged and considered in trial design [ 34 ].…”
Section: Discussionmentioning
confidence: 80%
“…As abdominal and back pain are very common symptoms among children and adolescents in general, further investigations and treatment need to be guided by acuity, intensity and associated findings 137 (Box 9). Even in the early stages of ADPKD, episodes of nonspecific abdominal pain are frequently reported by adults and tend to be underestimated by physicians 138 . However, patients might have a biased perception of pain, especially if investigations for abdominal pain led to their incidental diagnosis of ADPKD.…”
Section: Management Of Complications Abdominal Painmentioning
confidence: 99%
“…There are currently few effective drugs to treat the disease, and the treatment in the early stages of ADPKD mainly includes blood pressure control and regular follow-up [5,9]. However, research on the physiological and psychological burden of patients in the early stages of ADPKD is very limited, and the conclusions are conflicting [10]. Obviously, in the early stages of the disease, as a social individual, it is a critical period for ADPKD patients to set up families and have children.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that even in the early stages, polycystic kidney disease (PKD) imposes a physical and psychological burden on patients, resulting in a decline in their quality of life. If doctors are not aware of this, patients may feel frustrated [10][11][12]. Patients' fear of the disease and feelings of helplessness, as well as doctors' insufficient health education on ADPKD and its relevant knowledge, may both affect the fertility willingness of ADPKD patients because of their fear of the inheritance of the disease and the complications of pregnancy and even hinder them from forming a family [13][14][15].…”
Section: Introductionmentioning
confidence: 99%